Implementation of Regulatory Policy in Government Agency - Edward James Sinaga (Jurnal Ilmiah Kebijakan Hukum, 2022)
Legal reform is a necessity. Regulatory arrangement is one aspect of the legal reform program within the framework of national legal development. Regulation is the solution and foundation of law enforcement and government policies, thereby creating legal certainty and order and providing benefits to the community. However, regulation is an obstacle to development due to overlapping regulations, hyper regulations, conflicts of interest and authority. It can be seen that there is a judicial review of existing laws in the Constitutional Court and 1,765 regional regulations have been canceled. The legal reform program is carried out based on the Regulation of the Minister of Administrative and Bureaucratic Reform concerning the Road Map for Bureaucratic Reform 2020-2024. The regulation mandates the need to create a Legal Reform Index to measure the success of Legal Reform. This research was conducted to provide an overview of regulations and the formation of regulations as well as the implementation of regulatory policies for Government Agencies. This research is juridical-empirical and used a qualitative approach. From the results of this study, it was found that there are regulations in Indonesia that require amalgamation, simplification, and revocation. Considering this situation, legal reform is needed. This determination is seen from the Legal Reform Index. Policy Measurement of the legal reform index is useful for ensuring the quality of good laws and regulations following the principles, rules and objectives of the ideal formation and arrangement of laws and regulations.